Analisis Metode Magnetik pada Daerah Manifestasi Panas Bumi Karangrejo, Kabupaten Pacitan - Mayang Bunga Puspita; Cholisina Anik Perwita; Sukir Maryanto; Imam Suyanto (Yayasan Literasi Sains Indonesia, 2023)
Geothermal energy is one of the natural resources found in Pacitan Regency, alongside mining and geotourism. Geothermal manifestations in Pacitan Regency take the form of hot springs located at two points: Tinatar in the Punung District and Karangrejo in the Arjosari District. This research primarily focuses on magnetic measurement methods at the Karangrejo hot spring manifestation to provide information about its subsurface geological conditions. Data acquisition was conducted using 2 Proton Precision Magnetometers (PPM) of the Geotron G-5 brand as both base and rover instruments. The acquired data was processed with diurnal correction, IGRF correction, separation of residual-regional anomalies, and Reduce to Pole (RTP) transformation. The research results show magnetic anomaly variations in the study area ranging from -220 nT to 200 nT. Some geological structures that could potentially be associated with the Karangrejo hot spring manifestation are north-south trending faults and northeast-southwest trending faults, while the lithology of the study area is dominated by kaolin alteration and andesite rocks. It is estimated that the Karangrejo geothermal system is a fault-hosted geothermal system resulting from fault activity.